2014
DOI: 10.1002/app.40450
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose nanofibers prepared from TEMPO‐oxidation of kraft pulp and its flocculation effect on kaolin clay

Abstract: Cellulose nanofibers were prepared using TEMPO/NaBr/NaClO oxidation of kraft pulp and successive ultrasonic treatment, and the properties were characterized by conductimetric titration, X‐ray diffraction, and atomic force microscopy. The resulting product was then applied as an anionic microparticle to constitute a microparticulate system with cationic polyacrylamide (CPAM), to induce the flocculation of the kaolin clay suspension. The flocculation effect was evaluated by determining the relative turbidity of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
24
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(27 citation statements)
references
References 35 publications
(50 reference statements)
3
24
0
Order By: Relevance
“…So far only a few studies have reported synthesis of anionic cellulose nanofibers applied as flocculants (Jin et al, 2014;Suopajärvi et al, 2013). No studies have been published on the synthesis and evaluation of CNCs for the flocculation of microalgal biomass.…”
Section: Introductionmentioning
confidence: 99%
“…So far only a few studies have reported synthesis of anionic cellulose nanofibers applied as flocculants (Jin et al, 2014;Suopajärvi et al, 2013). No studies have been published on the synthesis and evaluation of CNCs for the flocculation of microalgal biomass.…”
Section: Introductionmentioning
confidence: 99%
“…In another research, cellulose nanofibers were prepared using TEMPO/NaBr/NaClO oxidation of Kraft pulp and successive ultrasonic treatment. The obtained nanofibers had cellulose I structure with a higher crystallinity than that of the Kraft pulp and a cross-section in the range of 3-5 nm (23).…”
Section: Cellulose Nanoparticlesmentioning
confidence: 98%
“…Recently, water‐soluble polymeric nanofibres have been considered as novel flocculants, because they can induce rapid flocculation and dewater mature fine tailings effectively. Cellulose nanofibres have been used in various wastewater treatment applications such as metal adsorption, mineral (quartz and hematite) flotation and flocculation, as well as flocculation of municipal wastewater and kaolin clay suspensions because of their abundance and low environmental impact . It has been shown that cellulose nanofibres can effectively flocculate kaolin suspensions, while also providing strong shear resistance of induced flocculation because of their very large specific surface areas and high crystallinity .…”
Section: Introductionmentioning
confidence: 99%
“…Cellulose nanofibres have been used in various wastewater treatment applications such as metal adsorption, mineral (quartz and hematite) flotation and flocculation, as well as flocculation of municipal wastewater and kaolin clay suspensions because of their abundance and low environmental impact . It has been shown that cellulose nanofibres can effectively flocculate kaolin suspensions, while also providing strong shear resistance of induced flocculation because of their very large specific surface areas and high crystallinity . However, despite promising results, cellulose nanofibres have to be used in conjunction with a coagulant or commercial flocculant to reach their full potential and are very sensitive to pH.…”
Section: Introductionmentioning
confidence: 99%